ZIC2 and ZIC3 promote SWI/SNF recruitment to safeguard progression towards human primed pluripotency - Ishtiaque Hossain; Pierre Priam; Sofia C. Reynoso; Sahil Sahni; Xiao X. Zhang; Laurence Côté; Joelle Doumat; Candus Chik; Tianxin Fu; Julie A. Lessard; William A. Pastor (Nature Communications, 2024)
Abstract The primed epiblast acts as a transitional stage between the relatively homogeneous naïve epiblast and the gastrulating embryo. Its formation entails coordinated changes in regulatory circuits driven by transcription factors and epigenetic modifications. Using a multi-omic approach in human embryonic stem cell models across the spectrum of peri-implantation development, we demonstrate that the transcription factors ZIC2 and ZIC3 have overlapping but essential roles in opening primed-specific enhancers. Together, they are essential to facilitate progression to and maintain primed pluripotency. ZIC2/3 accomplish this by recruiting SWI/SNF to chromatin and loss of ZIC2/3 or degradation of SWI/SNF both prevent enhancer activation. Loss of ZIC2/3 also results in transcriptome changes consistent with perturbed Polycomb activity and a shift towards the expression of genes linked to differentiation towards the mesendoderm. Additionally, we find an intriguing dependency on the transcriptional machinery for sustained recruitment of ZIC2/3 over a subset of primed-hESC specific enhancers. Taken together, ZIC2 and ZIC3 regulate highly dynamic lineage-specific enhancers and collectively act as key regulators of human primed pluripotency.